2017
DOI: 10.1371/journal.pone.0184594
|View full text |Cite
|
Sign up to set email alerts
|

Managerial attitudes and perceived barriers regarding evidence-based practice: An international survey

Abstract: Evidence-based practice (EBP) in management is still in its infancy. Several studies suggest that managers in businesses and other organizations do not consult the scientific evidence when making decisions. To facilitate its uptake, we need to better understand practitioner attitudes and perceived barriers related to EBP. In medicine and nursing, an abundance of research exists on this subject, although such studies are rare in management. To address this gap, we surveyed 2,789 management practitioners in Belg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
63
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 57 publications
5
63
1
7
Order By: Relevance
“…This lies in the fact that generating research evidence is time‐consuming and use of provided evidence needs some time to be appreciated. Practitioner time constraints also tend to limit the use of EBP because of perceived barriers in their work settings (Barends et al., ). Similarly, in this review, lack of time to read research findings, conduct research, and implement new ideas into practice was reported as one of the most common barriers to EBP across studies.…”
Section: Discussionmentioning
confidence: 99%
“…This lies in the fact that generating research evidence is time‐consuming and use of provided evidence needs some time to be appreciated. Practitioner time constraints also tend to limit the use of EBP because of perceived barriers in their work settings (Barends et al., ). Similarly, in this review, lack of time to read research findings, conduct research, and implement new ideas into practice was reported as one of the most common barriers to EBP across studies.…”
Section: Discussionmentioning
confidence: 99%
“…In Barend's study, most respondents base their decisions on personal experience (94%), knowledge acquired through formal education (71%), intuition (67%), advice from colleagues (64%), or insights provided by experts (63%). The minority of those managers interviewed replied that they base their decisions on findings from scientific research (33%) ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…These included internally developed data, best practice, stakeholders'/clients' expectations, instances of external practice, expert opinions, quantitative research, and qualitative research ( 16 , 22 ). Moreover, Barends et al listed four main evidence types which include following items: the best available scientific research, organizational data, professional experience and judgment, and stakeholders' values and concerns ( 29 ).…”
Section: Discussionmentioning
confidence: 99%